Notice of some points in Irish agricultural statistics - Connolly, James (Statistical and Social Inquiry Society of Ireland, 1879)
I now wish to make a brief communication of a most important and interesting discovery, if I may so call it, which I think I have made with regard to agricultural statistics. In poring over Thorn's article on the latter, I noticed, to my great surprise, that no mention whatever is made of the annual wool clip. Seeing that there are upwards of 4,500,000 sheep in the country, the value must be very considerable. In my opinion, it cannot on an average be less than #1,500,000 at the lowest. I may here observe that, owing to the present universal dullness of trade, there is this year a very heavy fall in the value of this article, as compared to the average of the last?say eight or ten?years.
Read before the Society, 25 June 1878
Keywords: Agriculture statistics; Wool industry; Irish agriculture; 314.15